Minahasa: A Land Gazed at by Early European Explorers - Yekyoum Kim (SUVANNABHUMI, 2025)
The present study explores and examines the socio-cultural landscape of Minahasa, North Sulawesi during a period of transition and significant transformation, as depicted by early European explorers, particularly following the advent of the Dutch Missionary Society (NZG; Nederlandsche Zendeling Genootschap) in the 1820s. Despite the paucity of primary sources from this period, the study examines the descriptions of three notable European explorers: Alfred Russel Wallace (1823-1913), Francis Henry Hill Guillemard (1852-1933), and Nicolaas Graafland (1827-1898). In fact, hitherto, Minahasa, North Sulawesi has received limited scholarly attention, in particular concerning the profound transformations that impacted from the 1820s onward. This study attempts to revisit early European explorers’ accounts as an alternative form of ethnographic data to reimagine the intricate socio-cultural fabric of Minahasan society during this transformative historical period. Such an attempt is intended to offer an invaluable ethnographic case study that contributes to Indonesian and Southeast Asian Studies, especially in examining the interaction between global and local communities shaped by colonialization since the 17th century. While furnishing a broad overview of the socio-cultural landscape of Minahasa, this study primarily focuses on the second half of the 19th century, whence the accounts of the three European explorers were written and subsequently published. Furthermore, the study situates these descriptions within the broader framework of early European exploration, offering insights into the global phenomenon of European expeditions as well as the individual backgrounds of the three explorers respectively.